MANAGING THE INFLUENCE OF MEDIA AND SOCIAL NETWORKS: THE SOCIO-PHILOSOPHICAL TRANSFORMATION OF YOUTH CONSCIOUSNESS - Madrakhimov, Vaisbay Bakhtiyarovich (Oriental Journal of History, Politics and Law, 2026)
This article is devoted to a socio-philosophical study of the impact of information and communication technologies (ICT) and mass culture on the patriotic consciousness of youth in the process of globalization. In accordance with international standards, this theoretical research is structured based on the IMRAD (Introduction, Theoretical Basis, Results, and Discussion) format. The aim of the research is to identify the trends of "mankurtism" and personal alienation emerging in the digital space, as well as to develop mechanisms for strengthening ideological immunity by fostering national pride and a culture of military patriotism among the youth. The results show that mass culture deforms the historical memory of young people, leading to virtual alienation. The necessity of interactive visualization of historical heritage using digital technologies to preserve patriotic consciousness is substantiated.